Comparative International Accounting / Fifth Edition - Nobes Christopher; Parker Robert (Prentice Hall Europe, 1998)
This book comprehensively examines the international dimensions of financial accounting and reporting. Preface, Acknowledgements, Context of International Accounting, Introduction, Causes of International Differences, Major International Differences in Financial Reporting, International Classification of Financial Reporting, Harmonization of Financial Reporting, Country Studies, Financial Reporting in the United Kingdom, Financial Reporting in the United States, Financial Reporting in the Netherlands, Financial Reporting in France, Financial Reporting in Germany, Financial Reporting in Japan, Financial Reporting in Nine Other Important Countries, Financial Reporting in Central and Eastern Europe and China, Issues in International Accounting, Consolidation, Foreign Currency Translation, Segment Reporting, Inflation Accounting, Analysis and Management Issues, International Financial Analysis, International Auditing, Classification and Harmonization of Corporate Income Taxes, Managerial Accounting, Glossary of Abbreviations, Index.